Marrying the perfect child — Middle class norms and intergenerational arrangements in the marriage corners of urban China - Pettier, Jean-Baptiste (Ethnography, 2020)
Caught in the context of a highly competitive development process, within the framework of a policy which limited their reproductive capacity to a single child, PRC urban families have, in recent decades, attached growing importance to their child's education, aiming to lead them to professional and personal success. This, however, also had an impact on the capacities of many young adults to marry early. In this context, the phenomenon of “marriage corners” mushroomed in large cities all over China beginning in the mid-2000s. Within China, this new practice generated criticism. These markets are seen as displaying conservative forms of marriage arrangement, the disregarding of romantic love, and forms of intergenerational power organization that may be considered backwards. However, by the criticisms it generates but as well the forms of relationships that it displays, the phenomenon can allow for a better understanding of the transformation of inter-generational relationships amongst urban middle-class, and on the norms framing the lives of the new generation.
CRIS-Team Scopus Importer:2023-03-21
Keywords: children; China; family; Marriage; norms; parents